Changes in the Russian Language in the Modern Period and Language Policy (Texas Journal of Philology, Culture and History, 2023)
The article discusses the changes that are taking place in the Russian language at the present time. In recent years, the Russian language has changed our lives and the person, just as decisively. It is natural, because the connection between the concepts of «language» and «society» is organic and inseparable. At the same time, there is no doubt that not all the innovations that characterize the modern language contribute to its development and enrichment. The article aims to identify the main lines that are changing in the Russian language and assess them